Synthetic Approaches to Contemporary Drugs that Contain the Cyclopropyl Moiety - Časar, Zdenko (Synthesis, 2020)
The U.S. Food and Drug Administration approved 18 new drugs that incorporate the cyclopropyl structural motif in the time frame from 2012 to 2018. This review provides an overview of synthetic approaches to these drugs with emphasis on the construction of the cyclopropyl moiety or its incorporation into the key building blocks for assembly of the highlighted drugs. Based on the structural diversity of these drugs, synthetic approaches for the construction and introduction of the cyclopropyl moiety into their structure are diverse and include: cycloalkylation (double alkylation) of CH-acids, catalytic cyclopropanation of alkenes with diazo compounds, the Simmons–Smith reaction, the Corey–Chaykovsky reaction, the Kulinkovich reaction, the Horner–Wadsworth–Emmons reaction, and cycloaddition. In addition, the cyclopropyl structure was also introduced into the drug substance intermediates via simple cyclopropyl-moiety-containing building blocks, such as cyclopropylamine, cyclopropanesulfonamide, cyclopropanecarbonyl chloride, and cyclopropylmagnesium bromide.1 Introduction2 Synthesis of Recently Approved Cyclopropyl-Moiety-Containing Drugs2.1 Cabozantinib2.2 Trametinib2.3 Simeprevir2.4 Ledipasvir2.5 Olaparib2.6 Tasimelteon2.7 Finafloxacin2.8 Paritaprevir2.9 Lenvatinib2.10 Lumacaftor2.11 Lesinurad2.12 Grazoprevir2.13 Glecaprevir2.14 Ozenoxacin2.15 Voxilaprevir2.16 Naldemedine2.17 Tezacaftor2.18 Tecovirimat3 Conclusion
Keywords: drugs; cyclopropyl moiety; total synthesis; asymmetric synthesis; catalysis